2017
DOI: 10.1016/j.adro.2017.03.003
|View full text |Cite
|
Sign up to set email alerts
|

ACR Appropriateness Criteria for external beam radiation therapy treatment planning for clinically localized prostate cancer, part II of II

Abstract: PurposeTo present the most updated American College of Radiology (ACR) Appropriateness Criteria formed by an expert panel on the appropriate delivery of external beam radiation to manage stage T1 and T2 prostate cancer (in the definitive setting and post-prostatectomy) and to provide clinical variants with expert recommendations based on accompanying Appropriateness Criteria for target volumes and treatment planning.Methods and materialsThe ACR Appropriateness Criteria are evidence-based guidelines for specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 110 publications
(192 reference statements)
2
17
0
Order By: Relevance
“…The treatments, and in particular radiation treatments, create another set of information needs. The radiation therapist is primarily responsible for providing this information from a patient-centred perspective [ 32 ]. Patients need to be warned about potential side effects of the radiation treatments and an explanation of the symptoms that they might be experiencing [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…The treatments, and in particular radiation treatments, create another set of information needs. The radiation therapist is primarily responsible for providing this information from a patient-centred perspective [ 32 ]. Patients need to be warned about potential side effects of the radiation treatments and an explanation of the symptoms that they might be experiencing [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the treatment of prostate cancer using hypofractionated radiotherapy is an emerging form of external beam radiotherapy which is an attractive option for low-risk patients who might not be candidates for brachytherapy or who find a 7–8-week course of daily conventional treatment (fractionated doses of 1.8–2 Gy daily fractions) prohibitive because of logistics or costs. [293031]…”
Section: Discussionmentioning
confidence: 99%
“…Hypofractionated treatment regimens usually deliver radiation doses ranging from 3.5 to 15 Gy per fraction in ≤5 daily fractions. [3031] Furthermore, a common and relevant use of IVD with diodes is the control or monitoring of total body irradiation (TBI) which requires detectors at the entrance and exit ports of the irradiation. [283233] TBI with external megavoltage photon beams may use parallel-opposed AP/PA or lateral fields.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, MR-only workflow introduces unique BMI considerations. For example, prostate RT plans are more precise with setup to intraprostatic gold or titanium fiducial implants (48), but these are visualized as signal void on conventional MRI sequences and poorly differentiated from calcifications. Maspero et al (49) reported that 3/48 fiducial implants were imprecisely and inaccurately identified by five radiation technologists when visualized only on MRI.…”
Section: How Is Biomedical Informatics Relevant To Mrigrt Currently?mentioning
confidence: 99%